Assessment of GFRP Reinforcement Bars Condition Based on Elastic Wave Propagation - RZEPKA, Anna; ZIAJA, Dominika; JUREK, Michał; WIATER, Agnieszka (Engineering Transactions, 2025)
New technologies in construction constitute a crucial element of effective development. Contemporary trends have led to increasing interest in composite materials, mainly due to their unique properties. The flexibility in shaping composite materials enables the production of reinforcing bars, providing a viable alternative to the widely used steel bars. The implementation of innovative solutions necessitates monitoring the performance of structures. Using information on the propagation of elastic waves is one of the non-destructive testing (NDT) methods for observing the construction behavior. An effort to employ this technique in the assessment of the anchoring condition and stress evaluation in glass fiber-reinforced polymer (GFRP) bars is presented in this study. During laboratory testing, samples of ribbed bars with diameters of Ø6 mm, Ø10 mm, and Ø16 mm were used (a total of 20 bars). Measurements were performed using laser Doppler vibrometry and piezoelectric transducers (PZT). Elastic waves were excited using a PZT sensor attached to one end of the bar, and the wave propagation was recorded in three ways: using a PZT sensor at the opposite end of the bar, using LDV at the opposite end, and on the sidewall. The research included samples of bars without anchorage, bars with anchorages (used for placement in a strength-testing machine), and specimens subjected to tensile testing (according to ISO 10406-1:2015). The collected signals were compared in both the time and frequency domains, considering variations in wave propagation due to different diameters, anchoring methods, and stress states. Based on the obtained results, it can be concluded that the analysis of the elastic wave propagation holds potential for assessing the condition of GFRP reinforcing bars.